The reproducibility of corrosion testing in supercritical water—Results of an international interlaboratory comparison exercise. (May 2016) - Guzonas, D.; Penttilä, S.; Cook, W.; Zheng, W.; Novotny, R.; Sáez-Maderuelo, A.; Kaneda, J.
Highlights: Round robin testing of corrosion (weight change) of three stainless steels in supercritical water. Results show small scatter within the same laboratory but large scatter between laboratories. Much of the variation can be attributed to differences between the test facilities. Correlation between weight change and autoclave refresh time. General agreement on the relative ranking of the corrosion resistance of the alloys tested. Abstract: A major challenge in supercritical water-cooled reactor development is the lack of a consistent alloy database. An international interlaboratory comparison test was organized to study the reproducibility of weight change data obtained for identical alloys under similar conditions in different facilities. This paper presents the test procedures, conditions, results, and additional characterization data. More variation in weight change was observed than expected. The scatter was small within the same laboratory, but large between different laboratories. Much of this variation appears to be attributable to differences in test facilities. The data generally agree on the relative ranking of the corrosion resistance.